2021
DOI: 10.1186/s40359-021-00649-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of academic performance during the covid-19 outbreak: impact of distance education on mental health, social cognition and memory abilities in an Italian university student sample

Abstract: Background This study aimed to investigate the impact of distance education (DE) on mental health, social cognition, and memory abilities in a sample of university students during the national COVID-19 lockdown in Italy and to identify the predictors of academic performance. Methods Two hundred and three students (76.4% women, mean age 24.3, SD ± 4.9) responded to an anonymous online cross-sectional survey between July 15 and September 30, 2020, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 64 publications
8
84
1
5
Order By: Relevance
“…For children of whom their parents reported more COVID-19 related worries, which was more often the case in DD children and in girls, both teacher-driven and assignment-driven teaching methods were rated as less effective. This finding is in line with the hypothesis and with previous research in the pandemic context (Cao et al, 2020 ; Giusti et al, 2021 ) and also consistent with prior research in the anxiety and depression domain showing that emotional-cognitive interference negatively influences task performance (Putwain et al, 2010 ). This can be explained by looking at the lower amount of working memory resources being available for cognitive tasks while worrying (Owens et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For children of whom their parents reported more COVID-19 related worries, which was more often the case in DD children and in girls, both teacher-driven and assignment-driven teaching methods were rated as less effective. This finding is in line with the hypothesis and with previous research in the pandemic context (Cao et al, 2020 ; Giusti et al, 2021 ) and also consistent with prior research in the anxiety and depression domain showing that emotional-cognitive interference negatively influences task performance (Putwain et al, 2010 ). This can be explained by looking at the lower amount of working memory resources being available for cognitive tasks while worrying (Owens et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…Studies underpin the importance of cold (working memory, planning, extent to engage in rehearsal, taking initiative…) and warm executive functions (e.g., emotion regulation, inhibition control; Mercader et al, 2018 ). In the context of COVID-19 it was for example shown in several studies that worries about getting infected with the disease (self or relative) are related to more negative affect and feelings of anxiety and depression (e.g., Giusti et al, 2021 ; Saravanan et al, 2020 ), especially in girls (e.g., Elmer et al, 2020 ; Rajkumar, 2020 ; Rodríguez-Hidalgo et al, 2020 ) and that these feelings in turn are negatively related to academic motivation and performance (Cao et al, 2020 ; Giusti et al, 2021 ).…”
Section: Opportunity-propensity Predictors For (Online) Learning (During Covid-19)mentioning
confidence: 99%
See 1 more Smart Citation
“…As some studies have shown ( Ochnik et al, 2021 ; Nomura et al, 2021 ; Giusti et al, 2021 ), this study also suggests that females have worse mental health than males.…”
Section: Discussionsupporting
confidence: 73%
“…In Italy, during the lockdown, students were reported to have experienced more psychological distress than workers ( Marelli et al, 2020 ). Risk factors associated with the worsening of students’ mental health during the COVID-19 pandemic include being female, participation in distance education, exposure to mass media, low levels of social support, previous mental health problems, financial problems, delays in academic activities, and living in a city ( Cao et al, 2020 ; Ma et al, 2020 ; Ochnik et al, 2021 ; Giusti et al, 2021 ). Smoking and consuming alcohol have also been associated with increased risk ( Nomura et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%